Ukraine : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper investigates the economic importance of institutions in Ukraine, and attempts to quantify the potential benefits of market-friendly structural reforms. The paper reviews some of the key findings of the development-accounting literature, which has tried to explain the significant differences in income that persist across countries. It introduces the stochastic-frontier approach, outlining its key assumptions and strengths, and results obtained with the stochastic-frontier model. The implications of the results for the specific case of Ukraine are discussed. The paper also analyzes external risks and opportunities for Ukraine.